Fadak in the Basri Novel: A Study in the Great Book of Tabaqat by Ibn Saad Al-Basri (230 )A.H - Abdel-Zahra Al-Derawi, Assist. Lect. Hadi (Basra studies journal, 2022)
The research attempts to clarify the opinion of the Basri school on the Fadak case by studying it in the book of the great layers of Ibn Saad Al-Basri (230 AH). it became clear to us that the Basri school is not much different from the rest of the Islamic schools in transmitting the narrations of the Fadak case, and it became clear that Fadak is one of the lands which gained after peace in certain war and became a property of the Messenger of God (), and he gave it as a heritage to his daughter, Lady Fatimah al-Zahra (), but the Caliph Abu Bakr took it back from her. Lady Fatima al-Zahra () had a strong personality and a great influence on the politics of the Islamic state after the Messenger of God’s transition or death ( ) to the supreme companion. It was possible for her to change the course of events in a different direction, based on her sanctity in the hearts of people, as she is the family of the Messenger (), and because she (according to a famous saying for the profit) harming her has is harming God and His Messenger (). The study also showed that the Caliphate rejected the invitation of Lady Al-Zahra () saying that the prophets do not inherit, and she cited a single hadith that was unique to the first Caliph.